Optimasi Proses Pengeringan Cara Sangrai Pada Pembuatan Tepung Ubi Jalar Dengan Suhu Terkendali - Imam Santosa; Endah Sulistiawati (Universitas Ahmad Dahlan, 2017)
Sweet potato (Ipomoea batatas L. Lam) potential to be used as industrial raw materials. Sweet potatoes have a high carbohydrate content that is in the fourth position after rice, corn, and cassava. Sweet potato flour can replace the function of wheat flour because when fermented with yeast will produce CO2 gas, which is needed in texture making and increase the volume of bread. As a raw material for cookies and cakes, the use of sweet potato flour can substitute 100% flour.The study offers a simple drying method and is expected to produce good quality sweet potato flour without chemical treatment. Small pieces or grated sweet potatoes will be roasted at a temperature and for a certain amount of time with oil bath-like tools until they are dry, then bolted.Over 250 grams of yam using a cheese solvent produces good dry chips. The best process at 100 0C takes 60 minutes, resulting in bright chip colors, sweet potato odor, flouriness, and a sweet tinge. 50 grams of purple, white, yellow and yellow honey consumed 90 minutes to 0% moisture content, yielding bright chip color according to original color, slightly sweet potato odor, flouriness, sweet tinge, 32-36,5% of rendemen.